2012
DOI: 10.1002/ibd.21841
|View full text |Cite
|
Sign up to set email alerts
|

Strategies in maintenance for patients receiving long-term therapy (SIMPLE): A study of MMX mesalamine for the long-term maintenance of quiescent ulcerative colitis*

Abstract: MMX mesalamine 2.4 g/day QD is effective for maintaining quiescence in patients with UC. Furthermore, adherence to prescribed treatment yielded lower rates of clinical recurrence. Continued education regarding the importance of long-term 5-aminosalicylic acid therapy is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Maintenance of remission rates of 61%–68% at 12 months with oral mesalamine has been reported 25,26. A meta-analysis by Ford et al reported that 42% of prescribed patients relapsed compared with 65% of patients taking placebo after 6 to 12 months of therapy 20.…”
Section: Current Management Of Ulcerative Colitismentioning
confidence: 99%
See 3 more Smart Citations
“…Maintenance of remission rates of 61%–68% at 12 months with oral mesalamine has been reported 25,26. A meta-analysis by Ford et al reported that 42% of prescribed patients relapsed compared with 65% of patients taking placebo after 6 to 12 months of therapy 20.…”
Section: Current Management Of Ulcerative Colitismentioning
confidence: 99%
“…Several randomized placebo-controlled trials have investigated the safety and efficacy of MMX mesalamine compared to placebo 25,26,39,5559. The efficacy of MMX mesalamine in inducing remission in active UC was demonstrated in two randomized, double-blind placebo-controlled trials39,55 (Table 2).…”
Section: Focus On Mmx® Mesalaminementioning
confidence: 99%
See 2 more Smart Citations
“…Kane et al [14] showed that mesalamine MMX at a dose of 2.4 g/day is effective for maintaining quiescence (no rectal bleeding) in ulcerative colitis patients.…”
Section: Key Pointsmentioning
confidence: 99%